2021
DOI: 10.1016/j.sjbs.2020.12.038
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and bioaccumulation of heavy metals in muscle tissues of five commercially important marine fish species from the Red Sea

Abstract: The study evaluated the nutritional quality and investigated the heavy metals concentration in muscle tissues of five commercially important marine fish species, including brownspotted grouper (Epinephelus chlorostigma), squaretail coralgrouper (Plectropomus areolatus), black pomfret (Parastromateus niger), goldbanded jobfish (Pristipomoides multidens), and blueskin seabream (Polysteganus coeruleopunctatus) from the Red Sea, Jeddah Coast, Saudi Arabia. Significant differences (p < 0.05) were observed in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
1
27
1
2
Order By: Relevance
“…Many studies have been conducted on the concentrations of PTMs in fish in many regions or countries, such as the Red Sea [19][20][21], India [22][23][24], Pakistan [14,[25][26][27][28], Indonesia [29,30], Persian Gulf or Iran [31][32][33][34][35], Bangladesh [36][37][38], Tanzania [39], Turkey [40], China [41][42][43], Mediterranean Sea [44,45], Aegean Seas of Turkey [46,47], Mexico [48], the Black Sea (Bulgaria), and the Ionian Sea (Italy) [49].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the concentrations of PTMs in fish in many regions or countries, such as the Red Sea [19][20][21], India [22][23][24], Pakistan [14,[25][26][27][28], Indonesia [29,30], Persian Gulf or Iran [31][32][33][34][35], Bangladesh [36][37][38], Tanzania [39], Turkey [40], China [41][42][43], Mediterranean Sea [44,45], Aegean Seas of Turkey [46,47], Mexico [48], the Black Sea (Bulgaria), and the Ionian Sea (Italy) [49].…”
Section: Introductionmentioning
confidence: 99%
“…mesopotamicus × C. macropomum while as the highest value was significantly noted in P. brachypomus. Younis et al (2021) while studying the nutritional profile of five significant marine fish species from Red Sea recorded the maximum value 2.97% of fat content in Plectropomus areolatus and minimum value 1.52% in P. coeruleopunctatus was noted. The study also revealed that the average amount of fat values was also seen to be statistically significant among different fish species.…”
Section: Fatmentioning
confidence: 99%
“…The results showed that P. brachypomus depicted the lowest ash content followed by C. macropomum while as the highest value was significantly noted in P. mesopotamicus . Younis et al (2021) while evaluating the nutritional profile of some commercially important marine fish species from Red Sea noted significantly highest value 6.72% of ash content in P. coeruleopunctatus and the lowest value 3.42% in case of P. niger .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations